2014
DOI: 10.1007/s11356-014-3368-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different sulfides on cadmium distribution during sludge combustion based on experimental and thermodynamic calculation approaches

Abstract: The effects of sulfur compounds on the migration of a semi-volatile heavy metal (cadmium) during sludge incineration were investigated with two methods, i.e., experiments in a tubular furnace reactor and thermodynamic equilibrium calculations. The representative typical sludge with and without the addition of sulfur compounds was incinerated at 850 °C. The partitioning of Cd among the solid phase (bottom ash) and gas phase (fly ash and flue gas) was quantified. The results indicate that sulfur compounds in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The homogenized sludge samples were passed through a sieve with a mesh size of , 150 lm and stored in jars at room temperature. Table 1 shows the properties of dried sewage sludge employed (Liu et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The homogenized sludge samples were passed through a sieve with a mesh size of , 150 lm and stored in jars at room temperature. Table 1 shows the properties of dried sewage sludge employed (Liu et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…This entire set is an effective experimental approach to simulate the migration and distribution of heavy metals in a real incinerator (Chiang et al, 1999). The detailed descriptions were presented in the literature of Liu et al, (2013Liu et al, ( , 2014Liu et al, ( , 2015. A quartz tube burner was placed in a glass-fiber-lined insulated steel shell, and a quartz boat moved by a quartz rod was used to feed the dry sludge into the combustion chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Wang et al, low temperature (800°C) and low oxygen concentration (10%) can be concluded to achieve reasonable control of heavy metal elements, but at the expense of reducing the combustion efficiency and destroying the integrity of the whole combustion process. Jing‐Yong Liu et al reported that sulphur can promote cadmium fixation in slag in the form of CdS and aluminosilicates among others in a local‐reducing atmosphere. The control of pollutants in the exhaust gas has also gained attention.…”
Section: Introductionmentioning
confidence: 99%
“…Alternately, Cadmium (Cd) is one of the most heavily regulated heavy metals in the standard for pollution control of MSW incineration, in which the Cd emission concentration limit is 0.1 mg/m 3 in China under the standard state of a concentration of 11% (v/v)O 2. To understand the transfer of Cd during the sludge incineration, it is necessary to study the influence of combustion conditions, such as temperature, gas composition, residence time and the presence of reactive compounds (chlorine, sulfur, or aluminosilicates), on the final Cd speciation in the residues (Han et al, 2006;Liu et al, 2013;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%